HUBUNGAN MOTIVASI BELAJAR DAN PERHATIAN ORANG TUA TERHADAP KESIAPAN BELAJAR SISWA KELAS 4 SDN 190 PEKANBARU - Restika Amelia Ningsih; Febrina Dafit (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Readiness to learn can be influenced by several interrelated factors, namely learning motivation and parental attention. This research aims to determine the relationship between learning motivation and the learning readiness of grade 4 students at SDN 190 Pekanbaru, the relationship between parental attention and the learning readiness of grade 4 students at SDN 190 Pekanbaru. Quantitative approach with associative research type. The sample was 67 students. Data analysis uses multiple correlation analysis. The results of this research reveal that there is a positive and significant relationship between Learning Motivation and Learning Readiness, where the higher the student's learning motivation, the higher the level of learning readiness. There is a positive and significant relationship between parental attention and learning readiness, where the higher the parental attention given to students, the higher the level of learning readiness. Simultaneously, learning motivation and parental attention have a simultaneous relationship with learning readiness, namely 52.2%, while the rest is determined by other variables not used in this research.